Effect of Unemployment and Inflation on Economic Growth in South Africa - Sekwati, Dimakatso; Dagume, Mbulaheni Albert (International Journal of Economics and Financial Issues, 2023)
The key macroeconomic objectives being pursued by any developing country are low unemployment, low inflation, and sustainable growth. The main aim of this study was to analyze the effect of unemployment and inflation on economic growth in South Africa for the period of 1994 to 2018, using quarterly data. The results of the unit root test using the Augmented Dickey Fuller and Phillips Perron tests showed that all the variables have a unit root in levels and became stationary after first differencing. The Johansen co-integration test outcomes showed that there is a long-run relationship among variables, and the Vector error correlation model confirmed that inflation and unemployment have a negative impact on economic growth. Furthermore, the results of the tests for White Heteroskedasticity, Jarque -Bera and Serial correlation LM reveal that there is no problem of Heteroskedasticity, data distribution or serial correlation respectively. The government should implement workable pricing regulations and enforce them to maintain stable price levels. The government should also through the Department of Higher Education and Training, establish a structure that connects the educational system with the industries in South Africa, allowing for the development of skills at the tertiary level and increasing employment.